2020
DOI: 10.2147/cia.s257079
|View full text |Cite
|
Sign up to set email alerts
|

<p>Physical Performance and Risk of Postoperative Delirium in Older Adults Undergoing Aortic Valve Replacement</p>

Abstract: Background: Delirium is a major risk factor for poor recovery after surgical aortic valve replacement (SAVR) and transcatheter aortic valve replacement (TAVR). It is unclear whether preoperative physical performance tests improve delirium prediction. Objective: To examine whether physical performance tests can predict delirium after SAVR and TAVR, and adapt an existing delirium prediction rule for cardiac surgery, which includes Mini-Mental State Examination (MMSE), depression, prior stroke, and albumin level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons for exclusion were no diagnosis by physician or research personnel (428 studies), no characterization of predisposing or precipitating factors (338 studies), retrospective study design (86 studies), not diagnosed by reference standard (108 studies), no multivariable model (43 studies), delirium assessment not conducted in person (25 studies), not cohort or case-control design (20 studies), sample included less than 50 patients (12 studies), abstract only (18 studies), cohort previously reported (3 studies), and pediatric population (1 studies). Ultimately, 315 studies…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in 40 different countries, with the plurality in the United States (86 studies [27.3%]), followed by China (48 studies [15.2%]) and the Netherlands (24 studies [7.6%]). Most studies were prospective cohort studies (296 studies…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, to make preoperative screening more clinically applicable there is a need for further studies to find other tests or test combinations that increase the preoperative predictive accuracy for postoperative delirium. 39 It is possible that tests with higher sensitivity for mild cognitive impairment are needed. For example, Montreal Cognitive Assessment (MoCA) in combination with Trial Making Test B may be more suitable for detection of mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%